(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
This article shows the evolution of the games and the financing instruments in detail of the public debt in Spain during the period 1996-2015. According to the review of them newsletters official of debt of the Bank of Spain, observed that the split of debt public have increased considerably to find a differential statistically significant in many of them (p >.05) and with a variability more high when governs the party Popular of court conservador-liberal. These results are displayed through an exploratory, descriptive and comparative study in relation to two temporary factors: political party in power and phase of the economic cycle.